Place of Humans in Creation: A Re-Reading of Psalm 8 - Setiawan, Charles Virgenius (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2024)
The natural damage and global warming witnessed in the past two decades were forecasted over 50 years ago by the scholar Lynn White, who asserted that these environmental challenges stem from a misinterpretation of human dignity in the Holy Scripture. This paper commences with an exploration of White’s allegations, subsequently endeavoring to discern the authentic essence of human dignity from Psalm 8 and its positioning within the context of creation. The findings of this study underscore that a misapprehension of human dignity’s essence can indeed lead to errors in the stewardship of nature. Conversely, when human dignity is accurately understood, the positive outcome entails the vigilant and responsible care of the natural environment.